Language and transient emotional states affect implicit cultural bias. Issue 5 (May 2019) - Ellis, Ceri; Hadden, Lowri; Jones, Manon Wyn
Bilinguals react to cultural information in a language-dependent fashion, but it is unknown whether this is influenced by the individual's emotional state. Here, we show that induced mood states increase cultural bias—measured using the Implicit Association Test (IAT)—but this effect occurs asymmetrically across languages. In the native language, bilinguals show a strong cultural bias, which is not influenced by mood. But in the non-native language, a relatively low cultural bias significantly increases as a function of a positive or negative mood. Our findings suggest that the native language promotes an inherent cultural bias, which is impervious to fluctuations in the bilingual's mood state. In the second language, however, bilinguals are culturally impartial, unless they are in a heightened mood state.